High erythromycin-resistant Campylobacter jejuni and C. coli among humans and chickens in Africa - Worku, M.; Gelaw, B.; Tesema, B.; Ferede, G.; Moodley, Arshnee; Grace, Delia (Hawassa University, 2022)
Human Campylobacter spp. enteritis is a common bacterial foodborne illness globally. C. jejuni and C. coli are implicated: chickens are carriers of these bacteria without showing clinical symptoms. The burden of antimicrobial resistant Campylobacter is increasing worldwide. However, there are limited data on the extent of antimicrobial resistance in Africa. Objective: This review aimed to estimate the pooled magnitude of antimicrobial resistance of Campylobacter jejuni and C. coli. Materials and methods: To fill this gap, we conducted a systematic review and meta-analysis following the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) Checklist. Literature search used relevant terms and phrases combined using the Boolean operators. The databases PubMed, Google Scholar, Hinnari, and Google were used to find relevant articles. All necessary data were extracted using a standardized data extraction format by two individuals independently. A quality assessment of selected articles was made using Newcastle–Ottawa scale adapted for cross sectional studies. Result: A total 12 studies were identified by this systematic review and meta-analysis. Of 1,142 isolates documented in the papers, 858 (75.1%) were C. jejuni and 284 (24.9%) were C. coli. We found C. jejuni showed lowest resistance level (21.2%) to ciprofloxacin and highest resistance level to trimethoprim-sulfamethoxazole(78.2%) whereas C. coli showed lowest resistance level (18.3%) to ciprofloxacin and highest level of resistance (82.7%) to azithromycin. The overall pooled magnitude of erythromycin resistance C. jejuni and C. coli among in human and chicken subjects was 51.0% and 54.0%, respectively. Conclusion: This systematic review and meta-analysis found high pooled magnitude of erythromycin resistant C. jejuni and C. coli among isolates from both humans and chickens in Africa. More One Health research is needed to give a clear picture on antimicrobial resistance and transmission dynamics of Campylobacter spp. in Africa, covering both humans and poultry.